ANALYSIS OF THE EFFECT OF DESTINATION IMAGE, ATTITUDE, AND SUBJECTIVE NORMS ON TOURIST VISIT INTENTION TO BEACH TOURISM IN BATAM - Chrissilia Widyasari Putri; Oda I.B Hariyanto (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2022)
This research was conducted to show that the aspect of Desire to Visit has a relationship with the components of Destination Image, Attitude, and Subjective Norms. Coastal tourism destinations are one of the destinations visited by domestic tourists. The quality of a destination creates a desire to visit that destination. This study uses the purposive sampling technique research method. IBM SPSS Statistics 20 is used as a program for data processing. Objects and samples in this study are domestic tourists in Batam who want to visit beach tourist destinations in Batam. This study used 411 respondents who were collected through distributing questionnaires on social media. The independent variables used in this study are destination image, attitudes, and subjective norms, the results of the study prove a significant positive effect on the desire to visit as the dependent variable.